2017
DOI: 10.1177/0954405417690553
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency blasting erosion arc machining of 50 vol.% SiC/Al matrix composites

Abstract: Blasting erosion arc machining (BEAM) is adopted to improve the machining efficiency of high fraction (50 vol.%) SiC/Al matrix composites. Results of the fractional factorial experiments and full factorial experiments indicate that the electrical parameters (peak current, pulse duration and pulse interval) are the main impact factors of the machining efficiency, and when the peak current is 500 A, the pulse duration is 8 ms and the pulse interval is 2 ms, the material removal rate reaches to 6000 mm 3 /min. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Compared to the EDM MRR of 140 mm 3 /min (peak current of 100 A) with a specific MRR 1.4 mm 3 / (AÁmin) [219], the efficiency of BEAM is much higher. Chen et al [283] also conducted experiments on the machining of 50% (volume fraction) SiC p /Al. The results revealed that even for the high-SiC fraction SiC p /Al composites, BEAM still could be used and the obtained MRR was as high as 7 500 mm 3 /min.…”
Section: Admmentioning
confidence: 99%
“…Compared to the EDM MRR of 140 mm 3 /min (peak current of 100 A) with a specific MRR 1.4 mm 3 / (AÁmin) [219], the efficiency of BEAM is much higher. Chen et al [283] also conducted experiments on the machining of 50% (volume fraction) SiC p /Al. The results revealed that even for the high-SiC fraction SiC p /Al composites, BEAM still could be used and the obtained MRR was as high as 7 500 mm 3 /min.…”
Section: Admmentioning
confidence: 99%